2021
DOI: 10.51494/jpdf.v2i1.419
|View full text |Cite
|
Sign up to set email alerts
|

Budaya Sekolah Dalam Mewujudkan Sekolah Sehat Nasional Di Sd Muhammadiyah 1 Ketelan Surakarta

Abstract: Tujuan penelitian yaitu untuk mendiskripsikan budaya sekolah, faktor pendukung dan penghambat, serta peran siswa dalam mewujudkan sekolah sehat nasional di (sekolah dasar) SD Muhammadiyah 1 Ketelan Surakarta.Narasumber dalam penelitian ini yaitu Kepala Sekolah, Wakil Kepala Sekolah (WKS) kurikulum, siswa, dan petugas unit kesehatan sekolah (UKS). Jenis penelitian menggunakan pendekatan kualitatif deskriptif dengan desain fenomenologi. Pengumpulan data dilakukan dengan teknik wawancara mendalam, observasi, dan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
4

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 0 publications
0
6
0
4
Order By: Relevance
“…Strengthening Child Friendly Schools is carried out in every activity in schools in a sustainable and sustainable manner (Farikah, 2019;Tria Vilian & Minsih, 2021). In the learning process, children are accustomed to sharing.…”
Section: Discussionmentioning
confidence: 99%
“…Strengthening Child Friendly Schools is carried out in every activity in schools in a sustainable and sustainable manner (Farikah, 2019;Tria Vilian & Minsih, 2021). In the learning process, children are accustomed to sharing.…”
Section: Discussionmentioning
confidence: 99%
“…Pembentukan karakter peserta didik begitu mendominasi pada perubahan komunikasi dan informasi dimana saat ini menjadi permasalahan yang begitu krusial dalam meningkatkan karakter siswa (Tria Vilian & Minsih, 2021). Pengaruh adanya kebebasan dan kemudahan dalam menggali informasi juga berdampak pada karakter peserta didik (Djunaidi, 2010).…”
Section: Pendahuluanunclassified
“…Simple actions like washing hands with soap, wearing masks, and consuming healthy food can also be done by children. "Clean and Healthy Living Behavior" (PHBS) is an individual effort followed by individuals, families, groups, and communities to promote learning experiences in maintaining cleanliness and health, ensuring a healthy body, strong immune system, and freedom from diseases (Tria Vilian & Minsih, 2021;Wardani et al, 2022). The practice of PHBS can be established through habits, as mentioned by.…”
Section: Introductionmentioning
confidence: 99%
“…Vegetables and fruits are still considered by the public as mere complements, whereas they should be regarded as balanced staple foods, according to health promotion initiatives in healthcare facilities, which have found that many people do not wash their hands with soap before eating. The lack of implementation of PHBS will have a detrimental impact on both the community and the educational environment, including the spread of various diseases (Mardhiati, 2019;Tria Vilian & Minsih, 2021).…”
Section: Introductionmentioning
confidence: 99%